A single intradermal injection of IFN-γ induces an inflammatory state in both non-lesional psoriatic and healthy skin - Johnson-Huang, Leanne M. (2012)
Psoriasis is a chronic, debilitating, immune-mediated inflammatory skin disease. As IFN-γ is involved in many cellular processes, including activation of dendritic cells (DCs), antigen processing and presentation, cell adhesion and trafficking, and cytokine and chemokine production, IFN-γ-producing Th1 cells were proposed to be integral to the pathogenesis of psoriasis. Recently, IFN-γ was shown to enhance IL-23 and IL-1 production by DCs and subsequently induce Th17 cells, important contributors to the inflammatory cascade in psoriasis lesions. To determine if IFN-γ indeed induces the pathways expressed in psoriasis lesions, a single intradermal injection of IFN-γ was administered to an area of clinically normal, non-lesional skin of psoriasis patients and biopsies were collected 24 hours later. Although there were no visible changes in the skin, IFN-γ induced many molecular and histological features characteristic of psoriasis lesions. IFN-γ increased a number of differentially expressed genes in the skin, including many chemokines concomitant with an influx of T cells and inflammatory DCs. Furthermore, inflammatory DC products TNF, iNOS, IL-23, and TRAIL were present in IFN-γ-treated skin. Thus, IFN-γ, which is significantly elevated in non-lesional skin compared to healthy skin, appears to be a key pathogenic cytokine that can induce many features of the inflammatory cascade of psoriasis.